IMPACT OF MERGER AND ACQUISITION ANNOUNCEMENT ON STOCK PRICE BEHAVIOUR ON BANKING SECTOR OF INDIA - Usapkar, Roshan; Dessai, Akshata Sinai (International Journal of Psychosocial Rehabilitation, 2020)
The main objective of bank merger is to increase the bank’s value in one way or another. This research paper scrutinizes the Impact of Merger and Acquisition Announcement on Stock Price Behaviour on banking Sector of India. In this study attempt is made to explore the effect of announcement of merger and acquisition on stock price behaviour of select companies from banking industry. In this paper, market model event study methodology has been used to find out the impact of announcement and found significant impact on stock prices during the window estimation period.